2020
DOI: 10.31234/osf.io/9jwx8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A primer on the role of boredom in self-controlled sports and exercise behavior

Abstract: Self-control is critical for successful participation and performance in sports and therefore has attracted considerable research interest. Yet, knowledge about self-control remains surprisingly incomplete and inconsistent. Here, we draw attention to boredom as an experience that likely plays an important role in sports and exercise (e.g., exercise can be perceived as boring but can also be used to alleviate boredom). Specifically, we argue that studying boredom in the context of sports and exercise will also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Supporting the link between boredom and self-control, preliminary evidence outside the sporting context shows that boredom makes it more difficult to adhere to a goal and selfcontrol moderates how well people deal with these difficulties (Danckert, Boylan, Seli, & Scholer, 2020;Bieleke, Martarelli, & Wolff, 2010;Wolff, Martarelli, Schüler, & Bieleke, 2020). Surprisingly, although the relevance of boredom in the context of repetitive athletic training has been emphasized already in 1926 (Davies, 1926), research on boredom and self-control in sports is scarce (Wolff, Bieleke, Martarelli, & Danckert, 2020). We know of only one study that has assessed the link between both concepts in the sporting context: Wolff and colleagues showed that boredom and self-control combine into distinct latent personality profiles that are linked to the weekly amount of exercise (Wolff, Bieleke, Stähler, & Schüler, 2021): One profile was characterized by a combination of low boredom and high self-control and this was linked with more exercise.…”
Section: Boredom As An Overlooked Self-control Demandmentioning
confidence: 99%
“…Supporting the link between boredom and self-control, preliminary evidence outside the sporting context shows that boredom makes it more difficult to adhere to a goal and selfcontrol moderates how well people deal with these difficulties (Danckert, Boylan, Seli, & Scholer, 2020;Bieleke, Martarelli, & Wolff, 2010;Wolff, Martarelli, Schüler, & Bieleke, 2020). Surprisingly, although the relevance of boredom in the context of repetitive athletic training has been emphasized already in 1926 (Davies, 1926), research on boredom and self-control in sports is scarce (Wolff, Bieleke, Martarelli, & Danckert, 2020). We know of only one study that has assessed the link between both concepts in the sporting context: Wolff and colleagues showed that boredom and self-control combine into distinct latent personality profiles that are linked to the weekly amount of exercise (Wolff, Bieleke, Stähler, & Schüler, 2021): One profile was characterized by a combination of low boredom and high self-control and this was linked with more exercise.…”
Section: Boredom As An Overlooked Self-control Demandmentioning
confidence: 99%